Diagnostic tests for amoebic liver abscess: comparison of enzyme - linked immunosorbent assay (Elisa) and counterimmunoelectrophoresis (CIE) - Marcos I. Restrepo; Zoraida Restrepo; Consuelo López Elsa Villareal; Aura Aguirre; Marcos Restrepo (Sociedade Brasileira de Medicina Tropical (SBMT), 1996)
The liver abscess is the most frequent extraintestinal complication of intestinal amoebiasis: its diagnosis is suggested by the clinical picture but it must be confirmed by paraclinic tests. Themost stringent diagnosis requires identification of E. histolytica. But this is possible only in a few cases. Serological tests greatly improve the diagnosis of this severe complication of amoebiasis. We compared the Enzyme Linfed Immunosorbent Assay and the Counterimmunoeletrophoresis techniques. Both techniques were used to detect amoebic antibodies in 50 control patients, 30 patients with liver abscess and 30 patients with intestinal amoebiasis. All the sera from control patients gave negative results iin both techniques. When analysing the sera from patients with intestinal amoebiasis, 10% of them were positive by ELISA but non by CIE. The sera of patients with liver abscess, we found that 90% were positive by the ELISA method and 66.6% by the CIE technique. In patients with amoebic liver abscess, the results showed that the ELISA was more sensitive than the CIE, as it presented a higher sensitivity (100%) than that of the CIE technique (66%). O abscesso hepático é a complicação mais freqüente da amebíase intestinal: o seu diagnótico sugere-se pelo quadro clínico, mas é confirmado pelos estudos paraclínicos. Para confirmar o diagnóstico precisa-se identificar a E. histolytica, o que é apenas possível em muito poucos casos. As provas sorolôgicas melhoram notadamente o diagnóstico das complicações severas da amebíase. Em nosso estudo comparamos o teste de ELISA e a Contraimunoeletroforese (CIE). Ambas as técnicas foram utilizadas para detectar anticorpos contra ameba em 50 pacientes sem amebíase, 30 pacientes com abscesso hepático e 30 com amebíase intestinal. Todos os soros dos pacientes sem amebíase foram negativos por ambas as técnicas. Quando analisamos os soros dos pacientes com amebíase intestinal, encontrou-se que 10% destes, foram positivos para ELISA, enquanto que nenhum o foi para CIE. Nos soros dos pacientes ...